Biological Evaluation and Molecular Docking of Protocatechuic Acid from Hibiscus sabdariffa L. as a Potent Urease Inhibitor by an ESI-MS Based Method - Hassan, Sherif T S; Švajdlenka, Emil (Molecules (Basel, Switzerland), 2017)
Studies on enzyme inhibition remain a crucial area in drug discovery since these studies have led to the discoveries of new lead compounds useful in the treatment of several diseases. In this study, protocatechuic acid (PCA), an active compound from Hibiscus sabdariffa L. has been evaluated for its inhibitory properties against jack bean urease (JBU) as well as its possible toxic effect on human gastric epithelial cells (GES-1). Anti-urease activity was evaluated by an Electrospray Ionization-Mass Spectrometry (ESI-MS) based method, while cytotoxicity was assayed by the MTT method. PCA exerted notable anti-JBU activity compared with that of acetohydroxamic acid (AHA), with IC50 values of 1.7 and 3.2 µM, respectively. PCA did not show any significant cytotoxic effect on (GES-1) cells at concentrations ranging from 1.12 to 3.12 µM. Molecular docking study revealed high spontaneous binding ability of PCA to the active site of urease. Additionally, the anti-urease activity was found to be related to the presence of hydroxyl moieties of PCA. This study presents PCA as a natural urease inhibitor, which could be used safely in the treatment of diseases caused by urease-producing bacteria.
Keywords: Humans; molecular docking; simulace molekulového dockingu; protocatechuic acid; ESI-Mass spectrometry; Molecular Docking Simulation; lidé; Hibiscus; hydroxybenzoáty; buněčné linie; hmotnostní spektrometrie s elektrosprejovou ionizací; Cell Line; kyseliny hydroxamové; urease inhibitors; Hibiscus sabdariffa L.; Hydroxybenzoates; Spectrometry, Mass, Electrospray Ionization; Urease; cytotoxicity; Hydroxamic Acids; ureasa